Obowiązek lojalności członka rady nadzorczej wobec spółki akcyjnej w warunkach wrogiego jej przejęcia - Sawicz, Witold (My University, 2014)
Przedmiotem rozprawy jest szeroko pojęte corporate governance. Szczegółowy przedmiot rozważań dotyczy obowiązku lojalności członka rady nadzorczej wobec spółki akcyjnej w warunkach wrogiego przejęcia. Przedmiot analizy stanowiły nie tylko regulacje XIII Dyrektywy UE i polskie ustawowe normy prawne, ale także pozaustawowe regulacje.Główna teza rozprawy brzmi: w warunkach wrogiego przejęcia obowiązek lojalności członka rady nadzorczej wobec spółki,określony na podstawie ustawowych i pozaustawowych regulacji, nie chroni w należyty sposób interesów spółki, jej akcjonariuszy i pozostałych interesariuszy. Przynajmniej w przypadku spółek publicznych należałoby implementować zasadę neutralności, sformułowaną w XIII Dyrektywie UE, w formie bezwzględnie obowiązującej normy prawnej.Podstawowym celem rozprawy była weryfikacja powyższej tezy. Drugim celem było sformułowanie, na podstawie otrzymanych wyjaśnień, wniosków de lege ferenda, w szczególności dotyczących sposobu implementacji XIII Dyrektywy UE do polskiego sytemu prawnego. Rozprawa stanowi wkład w naukowy dyskurs dotyczący zasad wykonywania mandatu członka rady nadzorczej polskiej spółki akcyjnej w warunkach wrogiego przejęcia.

The subject of this dissertation is widely understood corporate governance. The specific object of the analysis is the issue of the duty of loyalty of member of supervisory board toward joint-stock company in hostie takeover. The subject of the research in this study is not only the regulation of XIII Directive UE and Polish legal norms, but also other non-statutory regulations. The main thesis of this dissertation is that: in hostile takeovers of joint-stock companies, the duty of loyaltyof member of supervisory board toward company, as determined on the basis of statutory and non-statutory regulations, does not ensure adequate protection of interest of company, its shareholders and others stakeholders. At least in the instance of public companies there is the need for implementation of the rule of neutralisty, as formuleted in the Directive UE, in form of mandatory binding legal norm. The primary objective of this study was to verify above main thesis. The seconary objective was to formulate, on a basis of received explanations, de lege ferenda proposals, particulary concerning the implementation of XIII Directive UE into Polish legal system. This dissertation could provide a contribution to scientific discourse concerning the rule of performing mandate of member of supervisory board of Polish joint-stock company in hostie takeover.
The duty of loyalty of member of supervisory board toward joint-stock company in hostile takeover
Wydział Prawa i Administracji
Keywords: Rada nadzorcza; Supervisory board; Spółka akcyjna; Joint stock company; Wrogie przejęcie; Hostile takeover; Obowiązek lojalności; Duty of loyalty